Yeats, Postcolonialism, and Turn-of-the-Century Aesthetics - Gjurgjan, Ljiljana Ina (1999)
The author compares the situation in some European literatures at the turn of the last century with contemporary postcolonial lit. However, two pardigms cannot be seen as identical phenomena, because of different reclamations of space in the two periods, and different conceptions of the political and the cultural. The complexity of those relations are delineated on the example of Yeates' work and ideology. The author puts a special stress on epistemological questioning, mythical imagination, reclamation of time and space, and draws examples from various other European literatures and arts at that time.
Projekt MZOS
ENG